Multimodality cardiovascular imaging in the complete congenital absence of the pericardium: case report and brief literature review - Nelya Oryshchyn; Yuriy Ivaniv; Veronika Yevtukh; Anastasiya Oryshchyn (Heart Vessels and Transplantation)
Objective: Congenital absence of the pericardium (CAP) is a rare heart disorder, frequently misdiagnosed due to an unspecific clinical picture and leading to diagnostic challenges. The purpose of this case presentation is to show how cardiac imaging methods can aid in accurate diagnosis of CAP. Case presentation: A case of the complete congenital absence of the pericardium in a 40-year-old man with complaints on dyspnea and fatigue is presented. Echocardiography revealed a dilated right ventricle with good contractility; normal dimensions and function of the left ventricle, and normal heart valve function. Pulmonary hypertension and atrial septal defect were excluded during echocardiography. Computed tomography revealed abnormal heart axis rotation leftward and posteriorly, raising suspicion of CAP. The diagnosis was confirmed by cardiac magnetic resonance imaging . The diagnostic flowchart for the CAP is discussed. Conclusion: Multimodality cardiac imaging provides clues to the diagnosis of CAP.